Biomarker analysis of the ASPEN study comparing zanubrutinib with ibrutinib for patients with Waldenström macroglobulinemia - Tam, Constantine S; Opat, Stephen; D'Sa, Shirley; Jurczak, Wojciech; Lee, Hui-Peng; Cull, Gavin; Owen, Roger G; Marlton, Paula; Wahlin, Björn E; García-Sanz, Ramón; McCarthy, Helen; Mulligan, Stephen; et al. (Blood advances, 2024)
The phase 3 ASPEN trial (NCT03053440) compared Bruton tyrosine kinase inhibitors (BTKis), zanubrutinib and ibrutinib, in patients with Waldenström macroglobulinemia (WM). Post-hoc biomarker analysis was performed using next-generation sequencing on pretreatment bone marrow samples from 98 patients treated with zanubrutinib and 92 patients treated with ibrutinib with mutated (MUT) MYD88 and 20 patients with wild-type (WT) MYD88 treated with zanubrutinib. Of 329 mutations in 52 genes, mutations in CXCR4 (25.7%), TP53 (24.8%), ARID1A (15.7%), and TERT (9.0%) were most common. TP53MUT, ARID1AMUT, and TERTMUT were associated with higher rates of CXCR4MUT (P < .05). Patients with CXCR4MUT (frameshift or nonsense [NS] mutations) had lower very good partial response (VGPR) and complete response rates (CR; 17.0% vs 37.2%, P = .020) and longer time to response (11.1 vs 8.4 months) than patients with CXCR4WT treated with BTKis. CXCR4NS was associated with inferior progression-free survival (PFS; hazard ratio [HR], 3.39; P = .017) in patients treated with ibrutinib but not in those treated with zanubrutinib (HR, 0.67; P = .598), but VGPR + CR rates were similar between treatment groups (14.3% vs 15.4%). Compared with ibrutinib, patients with CXCR4NS treated with zanubrutinib had a favorable major response rate (MRR; 85.7% vs 53.8%; P = .09) and PFS (HR, 0.30; P = .093). In patients with TP53MUT, significantly lower MRRs were observed for patients treated with ibrutinib (63.6% vs 85.7%; P = .04) but not for those treated with zanubrutinib (80.8% vs 81.9%; P = .978). In TP53MUT, compared with ibrutinib, patients treated with zanubrutinib had higher VGPR and CR (34.6% vs 13.6%; P < .05), numerically improved MRR (80.8% vs 63.6%; P = .11), and longer PFS (not reached vs 44.2 months; HR, 0.66; P = .37). Collectively, patients with WM with CXCR4MUT or TP53MUT had worse prognosis compared with patients with WT alleles, and zanubrutinib led to better clinical outcomes.
Keywords: Piperidines; pyrazoly; Adenine; Waldenströmova makroglobulinemie; piperidiny; Humans; adenin; biologické markery; Pyrimidines; Pyrazoles; lidé; Biomarkers; Waldenstrom Macroglobulinemia; pyrimidiny; myeloidní diferenciační faktor 88; Myeloid Differentiation Factor 88